Dynamics of high frequency brain activity. Issue 1 (December 2017) - Moffett, Steven; O'Malley, Sean; Man, Shushuang; Hong, Dawei; Martin, Joseph
Abstract Evidence suggests that electroencephalographic (EEG) activity extends far beyond the traditional frequency range. Much of the prior study of >120 Hz EEG is in epileptic brains. In the current work, we measured EEG activity in the range of 200 to 2000 Hz, in the brains of healthy, spontaneously behaving rats. Both arrhythmic (1/f-type) and rhythmic (band) activities were identified and their properties shown to depend on EEG-defined stage of sleep/wakefulness. The inverse power law exponent of 1/f-type noise is shown to decrease from 3.08 in REM and 2.58 in NonREM to a value of 1.99 in the Waking state. Such a trend represents a transition from long- to short-term memory processes when examined in terms of the corresponding Hurst index. In addition, treating the 1/f-type activity as baseline noise reveals the presence of two, newly identified, high frequency EEG bands. The first band (ψ) is centered between 260–280 Hz; the second, and stronger, band is a broad peak in the 400–500 Hz range (termed ω). Both of these peaks display lognormal distributions. The functional significance of these frequency bands is supported by the variation in the strength of the peaks with EEG-defined sleep/wakefulness.